2014
DOI: 10.1002/app.41649
|View full text |Cite
|
Sign up to set email alerts
|

Improving the properties of reclaimed waste tire rubber by blending with poly(ethylene‐co‐vinyl acetate) and electron beam irradiation

Abstract: Non-degradable waste tire generation around the world is growing at an alarming rate. Diversifying the recycling route of these waste tires is essential to solve the problem. One way is to incorporate them into polymers and convert them into new products. However, incorporation of ground tire rubber into thermoplastics has been hampered due to lack of toughness and adhesion between phases. To address the issue, this study utilized reclaimed waste tire rubber (RTR) instead; and evaluated the properties of RTR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 161 publications
(251 reference statements)
1
16
0
1
Order By: Relevance
“…Peroxide crosslinking seems to render mixed results. Though, it has not been critically discussed in any of the literature, this could be due to presence of additives such as stabilizers and antioxidant in the GTR/RTR which stabilizes and/or scavenges the radical formed using peroxides [95]. This is also supported by the observation in ionizing radiation cross-linked blends where the improvements recorded are rather low.…”
Section: Effect Of Crosslinkingmentioning
confidence: 77%
“…Peroxide crosslinking seems to render mixed results. Though, it has not been critically discussed in any of the literature, this could be due to presence of additives such as stabilizers and antioxidant in the GTR/RTR which stabilizes and/or scavenges the radical formed using peroxides [95]. This is also supported by the observation in ionizing radiation cross-linked blends where the improvements recorded are rather low.…”
Section: Effect Of Crosslinkingmentioning
confidence: 77%
“…Moreover, analysis of literature data showed that the tensile strength of obtained materials is significantly higher than the 2.0 MPa determined for reclaimed GTR/EVA system in the ratio of 70/30%wt. [ 44 ]. Finally, GTR/rPE/TOR 90/10/9 proposed by a different research group [ 28 ] shows tensile strength at 2.1 MPa, elongation at break at approx.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is related to the higher thermal stability of thermoplastics when comparing to GTR, which is very important during high-temperature processing via extrusion, injection, or compression molding. For example, Ramarad et al [ 44 ] studied the thermal stability of reclaimed GTR/EVA blends by thermogravimetric analysis. The results indicated that volatile compounds content in reclaimed GTR is 8.25%wt., while for reclaimed GTR modified by 30%wt.…”
Section: Resultsmentioning
confidence: 99%
“…Breakage strength may also be adversely affected, although there are known cases (the use of regenerate from integral tire) [10] when the influence is positive. Moisture absorption of the reclaimed rubber is relatively large in comparison with the compositions of new tires and therefore its use is not recommended when water absorption is an essential criterion [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%